PENGARUH SENAM AEROBIK TERHADAP KUALITAS TIDUR DAN SINDROM MAKAN MALAM PADA MAHASISWI OBESITAS - Agita Dianingsih; Fillah Fithra Dieny; Nuryanto Nuryanto; Ahmad Syauqy (PERSATUAN AHLI GIZI INDONESIA, 2022)
The prevalence of obesity is high in women aged 18 years which is 21.8 percent. Twenty-two-year-old female students are one of the populations at risk of poor sleep quality and night-eating syndrome. Regular aerobic exercise can have a positive effect on sleep quality followed by a reduction in night eating syndrome. This study aims to analyze the effect of aerobic exercise on sleep quality and dinner syndrome in obese female students. The study was a quasi-experimental design with a pre-post test control group design conducted on 22 subjects. Inclusion criteria were female students aged 19-24 years determined by consecutive sampling. Subjects were divided into 2 treatment and control groups. The treatment was given aerobic exercise intervention for 4 weeks. As well as obesity management education and balanced nutrition using leaflets for both groups. Sleep quality data using the Pittsburgh Sleep Quality Index and night eating syndrome using the Night Eating Questionnaire and food recall 3x24 hours. Statistical analysis using Independent T-Test, and Mann-Whitney test. There was a change before and after the aerobic exercise intervention in sleep quality (-1-(-3)) and night eating syndrome (-3-(-10)), treatment group (p0.001 and p=0.003). Meanwhile, the control group did not experience significant changes. Giving aerobic exercise for 4 weeks can improve sleep quality and reduce night eating syndrome significantly